Optimization of medium composition for probiotic powder inoculum using the response surface methodology. Issue 1 (June 2021) - Rohmatussolihat,; Ridwan, R; Widyastuti, Y; Sari, N F; Fidryanto, R; Astuti, W D
Abstract: Probiotic as feed additives have been developed as alternatives to improve animal health and productivity. Probiotics are live microorganisms that confer health benefits to the hosts by improving intestinal microbial balance. The aims of this study was to optimize the formulation of probiotic powder inoculum from Lactobacillus plantarum TSD-10 BTCC 531 using Response Surface Methodology with Central Composite Design (RSM-CCD). The RSM-CCD was prepared using three variables, consist of; skim milk, maltodextrin and CaCO3, with five-level combinations. The drying process of the probiotic powder inoculum used a freeze dryer for 16 hours. The L. plantarum TSD-10 BTCC 531 survival amounts were measured by the total plate count method. Statistical analysis showed that the viability of L. plantarum TSD-10 BTCC 531 was significantly affected by skim milk and CaCO3 . Estimated optimum conditions of the factors on the bacterial viability have consisted of 5% (w/v) skim milk, 1.547% (w/v) maltodextrin, 0.5% (w/v) CaCO3, and with a maximum L. plantarum TSD-10 BTCC 531 number of surviving results at 1.945 × 10 12 CFU/g, which significantly increased by 34.9%. The results of the validation experiments showed that the cell number of probiotic reaches 2.17 × 10 12 CFU/ or 11.43% more than the predicted cell number of L. plantarum TSD-10 BTCC 531 from the regression model produced.